Utilizing PhET simulation in a guided inquiry-based virtual biology lab to improve science literacy among junior high school students - Priadi, Median Agus; Lengkana, Dewi; Yosita, Diana (Assimilation: Indonesian Journal of Biology Education, 2025)
This study aims to determine the effect of implementing a guided inquiry model with assistance PhET simulation as virtual laboratory towards improving students' scientific literacy skills. This quasi-experimental study used a Pretest Posttest Non-Equivalent Control Group design. The population consisted of 5 classes with a total of 134 students, while the sample was taken from two classes totaling 51 students, selected using the Purposive Sampling technique. The experimental class was given treatment using a guided inquiry model assisted by Virtual Laboratory PhET Simulation, while the control class used a guided inquiry model. Data on students' scientific literacy skills were obtained from pretest and posttest scores. To determine the increase in scientific literacy, an N-gain test was conducted. The results of the N-gain test showed an average increase in the experimental class's scientific literacy skills of 0.53 (moderate category) and the control class of 0.28 (low category). Furthermore, an Independent Sample T-Test was conducted to determine the effect of variable X on variable Y, obtained Sig.0.00. Based on the Independent Sample T-Test, it is known that there is an effect of implementing a guided inquiry model assisted by Virtual Laboratory PhET Simulation on improving scientific literacy skills. The effect size test was also conducted and obtained a value of 1.78 with an interpretation of the effectiveness level in the large category. Thus, it can be concluded that the implementation of the guided inquiry model assisted by the Virtual Laboratory PhET Simulation has a significant effect on improving students' scientific literacy skills.